PENERAPAN KURIKULUM 2013 MATA PELAJARAN BAHASA INDONESIA DI SMP NEGERI 1 KECAMATAN PAYAKUMBUH DALAM PEMBELAJARAN TEKS CERPEN - Deviani, Elsa; Nursaid, Nursaid; Hafrison, Mohd. (Universitas Negeri Padang, 2018)
This research is purposedly done to describe activities of short stories learning implementation in Curriculum of 2013 in the stage of (1) building knowledge of the field, (2) modelling, (3) joint construction of the text, (4) independent construction of the text in SMP Negeri 1 Kecamatan Payakumbuh. The type of this research is qualitative research which use descriptive method. Observation and interview methods are used in the data collecting proccess. The output of the research shows that the teachers of SMP Negeri 1 Kecamatan Payakumbuh building knowledge of the field by using three kind of activities. They are introduction activity, main activity, and closing activity. Modelling stage is done by giving the students short stories that are cut from newspapers. Joint construction of the text is done in a group by using continue-the-storie technic. The independent construction of the text is done by giving the students different theme of stories, and then they are asked to produce, edit, and publicate the stories in the wall magazine.Kata Kunci: pelaksanaan pembelajaran, Kurikulum 2013, teks cerpen